Reviving peace talks in Cyprus: Diplomatic innovation and the new UN envoy. Creative diplomacy needed for breakthrough in long-standing conflict - Erol Kaymak (Stiftung Wissenschaft und Politik (SWP), 2024)
On January 5, 2024, UN Secretary-General António Guterres appointed María Ángela Holguín Cuéllar as his Personal Envoy on Cyprus. Her role is to determine the 'common ground' from which peace talks can be resumed after standing still since 2017. The shift in Greece-Turkey relations holds regional potential, which could lead to progress in Cyprus. Nonetheless, there is an urgent need for creative diplomacy given the stalemate and changing regional dynamics. A new agenda based on regional integration could further efforts to establish common ground through process innovation, phased negotiations, deadlines, and the establishment of safeguards against future stalls.
Keywords: 320; María Ángela Holguín Cuéllar; Personal Envoy on Cyprus; UN Secretary-General António Guterres; peace talks; Cyprus; Turkey; regional integration; United Nations Peacekeeping Force in Cyprus (UNFICYP)